Factors Associated with the Competency of School Students in Using CEHRD Learning Portal for Mathematics - Joshi, Dirgha Raj; Khanal, Bishnu; Sharma Chapai, Krishna Prasad (Education and Development, 2025)
This study explores the factors influencing school students’ competency in using the Center for Education and Human Resource Development (CEHRD) learning portal for mathematics learning in Nepal. The cross-sectional survey design was utilized in the research among 836 school students of Kathmandu. Frequency, percentage, Mann-Whitney U, Kruskal-Wallis H tests as well as path analysis were the major statistical techniques applied to this research. The results indicate that students with regular access to both mobile phones and laptops, and those who spend more than one hour daily using them for mathematics, demonstrate higher competency in using the CEHRD learning portal. While the school type and the study level influence competency indirectly through device access, gender differences are found minimal. The findings from scatter plots and path models underscore that time of usage mediates the effect of device access, and access mediates the impact of school-related variables. The study highlights the significance of equitable digital access and structured engagement in promoting the effective use of the learning platforms. The findings have important implications for policymakers, educators, and platform designers in enhancing digital equity and optimizing the portal use for improved mathematics learning outcomes.